New media and cross-cultural adaptation: a bibliometric analysis using VOSviewer - Jiang, Meilian; Abdul Latiff Ahmad,; Jamaluddin Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
A growing scholarly interest focused on new media and cross-cultural adaptation research, but a bibliometric analysis with VOSviewer software still needs to be improved. The paper aims to review the literature on new media and cross-cultural adaptation during the past two decades, analyse the current research on new media and cross-cultural adaptation, get an overview of current research, identify the heated topics, and propose future directions. This paper examined 1,1518 English-language articles published in the Web of Science database from 2003 to 2023 using bibliometric techniques and the VOSviewer software. The methodology analysed the variables such as development time, Top 10 countries, organisations, authors, articles, journals, and co-occurrence keywords in the bibliometric analysis. A review of the past 20 years shows a significant increase in excellent research publications on new media and cross-cultural adaptation. Regarding the region of publications, the number of publications in the United States is the absolute leader, followed by China, the United Kingdom, Australia, Spain, and Germany. However, the highest average number of citations is for Germany. As seen from the five categorised clusters, cross-cultural studies on social media use, Internet addiction, psychological health issues, and international students have become a growing concern in recent years. Future research on new media and cross-cultural adaptation may move toward exploring international students' social media usage and psychological adaptations.